Trombone Soloist Performance with The Repertoire "Sonata In F Minor", "Djoget Hitam Manis," and "Dancing Queen" - Muhammad Rheinhard Afana; Hafif HR; Ibnu Sina; Hadaci Sidik; Ofa Yutri (Musica: Journal of Music, 2026)
This solo trombone recital is a practice-based research aimed at exploring the interpretative capacity and flexibility of the trombone as a solo instrument through the performance of three selected repertoires: Sonata in F Minor by Georg Philipp Telemann, Joget Hitam Manis arranged in a Malay–tango style, and Dancing Queen by ABBA. The research employs a performance-based methodology consisting of preparation, rehearsal process, performance, and post-performance evaluation. The results indicate that each repertoire requires a distinct technical and interpretative approach in terms of articulation, phrasing, dynamics, and stylistic understanding. Sonata in F Minor emphasizes the mastery of Baroque idioms and ornamentation, Joget Hitam Manis demands the ability to blend Malay musical characteristics with tango elements, while Dancing Queen requires adaptation of vocal idioms and pop–disco grooves into trombone performance. This recital demonstrates that the trombone possesses broad interpretative flexibility and is capable of functioning as a communicative solo instrument across diverse musical genres.